Model Pembelajaran Probing-Prompting: Pengaruhnya terhadap Hasil Belajar Biologi Siswa Kelas XI SMA - Nursafika; Pujiastuti, Indah Panca; Fausan, Muhammad Mifta (Indo-MathEdu Intellectuals Journal, 2026)
Effective biology learning should involve students actively in the learning process. However, based on a preliminary study, students’ learning outcomes were still relatively low because the learning process was teacher-centered. This study aimed to determine the effect of the Probing-Prompting learning model on students’ biology learning outcomes. This research used a quasi-experimental method with a nonequivalent control group design. The study was conducted at SMAN 2 Tapalang during the even semester of the 2024/2025 academic year. The population consisted of 44 students, and the sampling technique used was total sampling, where class XI MIPA 1 served as the experimental class and class XI MIPA 2 served as the control class. Data were collected using a learning outcome test consisting of 15 multiple-choice questions and 5 essay questions administered as a pretest and posttest. The data were analyzed using descriptive and inferential statistics through the independent sample t-test, after fulfilling the normality and homogeneity prerequisite tests. The results of the independent sample t-test showed a significance value of 0.00 (<0.05), indicating that the Probing-Prompting learning model had a statistically significant effect on students’ biology learning outcomes.